A kind of anti-reduction low temperature sintered C0G ceramic dielectric material and its preparation method and application
By using mechanical mixing and calcining of SrZrO3, Mg2SiO4, SrTiO3 and other materials to prepare ceramic materials, the problem that existing dielectric materials cannot be sintered below 1050℃ is solved, and the high dielectric constant and reduction resistance of ceramic materials are achieved, which is suitable for the high frequency requirements of copper electrode MLCC.
Patent Information
- Application Number
- CN202311008607.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-10
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2043-08-10
AI Technical Summary
The existing dielectric materials cannot be sintered into porcelain below 1050°C, and cannot meet the high-frequency requirements of copper electrode multi-layer sheet ceramic capacitors.
Ceramic materials including SrZrO3, Mg2SiO4, SrTiO3, modifier and sintering additive are prepared by mechanical mixing and calcining to ensure that the ceramic materials have high dielectric constant, good anti-reduction properties and electrochemical properties.
The ceramic material is sintered into ceramics below 1050°C, with high dielectric constant and good reduction resistance. It is suitable for the preparation of copper electrode MLCC and meets the needs of high frequency.
Smart Images

Figure BDA0004390252400000011 
Figure BDA0004390252400000021 
Figure BDA0004390252400000022
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of ceramic materials, and in particular relates to a ceramic material and a preparation method and application thereof. Background Art
[0002] With the rapid development of the mobile communication industry, electronic components are constantly developing in the direction of miniaturization, high performance and low cost, so multilayer ceramic capacitors (MLCC) came into being. Multilayer ceramic capacitors include dielectric materials and electrodes, and the current electrodes are mainly silver-palladium electrodes. However, with the increasing market demand for the fifth-generation mobile communication technology (5G), higher requirements are placed on electronic components, and the frequency of capacitors needs to be greatly increased; MLCCs prepared with copper electrodes can better meet the high-frequency requirements of microwave capacitors than MLCCs prepared with silver-palladium electrodes, which is in line with the development trend of modern communication technology. The use of copper electrodes to prepare MLCCs has become the forefront and hot spot of current research.
[0003] MLCCs using metal copper electrodes must meet the requirement that the dielectric material and the copper electrode slurry be co-fired under low oxygen partial pressure or reducing atmosphere, that is, the metal conductivity of the copper electrode and the good comprehensive electrical properties of the MLCC, such as low loss and high insulation resistance, must be maintained at the same time. Therefore, the dielectric material used in copper electrode MLCCs must be able to be sintered into porcelain below 1050°C and have good anti-reduction properties. Most of the existing dielectric materials are porcelain materials sintered at medium and high temperatures (1150-1350°C), which cannot meet the requirements for preparing copper electrode MLCCs. Summary of the invention
[0004] In view of this, the present invention provides a ceramic material and a preparation method and application thereof. The ceramic material provided by the present invention has a high dielectric constant and can be used to prepare copper electrode MLCC.
[0005] In order to solve the above technical problems, the present invention provides a ceramic material, comprising the following components in parts by weight:
[0006]
[0007] The modifier includes at least four substances among MnO2, MgO, Y2O3, Dy2O3, Nd2O3, Sm2O3 and Al2O3; the sintering aid includes at least four substances among Li2CO3, H3BO3, BaCO3, ZnO and SiO2.
[0008] Preferably, the modifier comprises the following components in parts by weight:
[0009]
[0010] The mass fractions of at least two substances among MgO, Dy2O3, Nd2O3, Sm2O3 and Al2O3 cannot be 0 at the same time.
[0011] Preferably, the sintering aid comprises the following components in parts by weight:
[0012]
[0013] Preferably, the preparation method of the sintering aid comprises the following steps:
[0014] The lithium source, boron source, barium source, zinc source and silicon source are mixed according to the element ratio in the sintering aid and then calcined to obtain the sintering aid; the calcination temperature is 550-590° C. and the calcination time is 2.5-3.5 hours.
[0015] The present invention also provides a method for preparing the ceramic material described in the above technical solution, comprising the following steps:
[0016] The ceramic material is obtained by mechanically mixing SrZrO3, Mg2SiO4, SrTiO3, a modifier and a sintering aid.
[0017] Preferably, the preparation method of SrZrO3 comprises the following steps:
[0018] SrCO3 and ZrO2 are mixed and calcined to obtain the SrZrO3;
[0019] The calcination temperature is 1180-1220° C., and the calcination time is 2-3 hours.
[0020] Preferably, the preparation method of Mg2SiO4 comprises the following steps:
[0021] Mixing Mg(OH)2 and SiO2 and calcining them to obtain the Mg2SiO4;
[0022] The calcination temperature is 1180-1220° C., and the calcination time is 1.8-2.5 hours.
[0023] Preferably, the preparation method of SrTiO3 comprises the following steps:
[0024] SrCO3 and TiO2 are mixed and calcined to obtain the SrTiO3;
[0025] The calcination temperature is 1080-1120° C., and the calcination time is 2-3 hours.
[0026] The present invention also provides the use of the ceramic material described in the above technical solution or the ceramic material prepared by the preparation method described in the above technical solution in a multilayer ceramic capacitor.
[0027] Preferably, the electrodes in the multilayer ceramic capacitor are copper electrodes.
[0028] The present invention provides a ceramic material, comprising the following components in parts by mass: 79.80-96.10 parts of SrZrO3, 0.63-17.55 parts of Mg2SiO4, 2.55-3.60 parts of SrTiO3, 0.8-4.1 parts of a modifier and 8.00-10.5 parts of a sintering aid; the modifier comprises at least four substances selected from MnO2, MgO, Y2O3, Dy2O3, Nd2O3, Sm2O3 and Al2O3; the sintering aid comprises at least four substances selected from Li2CO3, H3BO3, BaCO3, ZnO and SiO2. The temperature variation coefficient of the ceramic material provided by the present invention meets the requirements of C0G dielectric ceramic materials, has a high dielectric constant, good anti-reduction properties and electrochemical properties; the copper electrode MLCC prepared by using the ceramic material provided by the present invention as a dielectric material has the characteristics of low loss and high insulation resistance. DETAILED DESCRIPTION
[0029] The present invention provides a ceramic material comprising the following components in parts by weight:
[0030]
[0031] The modifier includes at least four substances among MnO2, MgO, Y2O3, Dy2O3, Nd2O3, Sm2O3 and Al2O3; the sintering aid includes at least four substances among Li2CO3, H3BO3, BaCO3, ZnO and SiO2.
[0032] In terms of mass percentage, the ceramic material provided by the present invention comprises 79.8 to 96.1 parts of SrZrO3, preferably 79.8 to 88.9 parts. In the present invention, the preparation method of SrZrO3 preferably comprises the following steps:
[0033] SrCO3 and ZrO2 are mixed and calcined to obtain the SrZrO3.
[0034] In the present invention, the SrCO3 is preferably analytically pure, and the ZrO2 is preferably analytically pure. In the present invention, the molar ratio of SrCO3 and ZrO2 is preferably 1:1. In the present invention, the mixing is preferably carried out under ball milling conditions. In the present invention, the dispersant for ball milling is preferably water, and the water is preferably deionized water. In the present invention, the grinding balls for ball milling are preferably zirconia balls; the rotation speed of the ball mill is preferably 190 to 210 rpm, more preferably 200 rpm; the time of the ball milling is preferably 7 to 9 hours, more preferably 7.5 to 8.5 hours.
[0035] In the present invention, the ball milling step preferably further comprises: drying the ball milled mixture. In the present invention, the drying step is preferably oven drying, and the oven drying temperature is preferably 110 to 120° C., more preferably 115 to 118° C.; the oven drying time is preferably 6 to 8 hours, more preferably 6.5 to 7 hours.
[0036] In the present invention, the calcination temperature is preferably 1180-1220°C, more preferably 1200-1210°C; the calcination time is preferably 2-3 hours, more preferably 2.5-2.8 hours. In the present invention, the calcination is preferably carried out in a muffle furnace.
[0037] In the present invention, the SrZrO3 can preliminarily determine the comprehensive properties of the ceramic material, such as the dielectric constant and the temperature coefficient; meanwhile, the SrZrO3 has a certain anti-reduction property, which is beneficial to improve the anti-reduction property of the ceramic material.
[0038] Based on the mass fraction of SrZrO3, the ceramic material provided by the present invention includes 0.63 to 17.55 parts of Mg2SiO4, preferably 7.95 to 8.55 parts. In the present invention, the preparation method of Mg2SiO4 preferably includes the following steps:
[0039] Mg(OH)2 and SiO2 are mixed and calcined to obtain the Mg2SiO4.
[0040] In the present invention, the Mg(OH)2 is preferably analytically pure, and the SiO2 is preferably analytically pure. In the present invention, the molar ratio of the Mg(OH)2 and SiO2 is preferably 2:1. In the present invention, the mixing is preferably carried out under ball milling conditions. In the present invention, the dispersant for ball milling is preferably water, and the water is preferably deionized water. In the present invention, the grinding balls for ball milling are preferably zirconia balls; the rotation speed of the ball mill is preferably 190 to 210 rpm, more preferably 200 rpm; the time of the ball milling is preferably 5 to 6 hours, more preferably 5.5 to 5.8 hours.
[0041] In the present invention, after the ball milling, the process preferably further comprises: drying the ball milled mixture. In the present invention, the drying is preferably oven drying, and the oven drying temperature is preferably 110 to 120° C., more preferably 115 to 118° C.; the oven drying time is preferably 6 to 8 hours, more preferably 6.5 to 7 hours. In the present invention, the oven drying is preferably carried out in an oven.
[0042] In the present invention, the calcination temperature is preferably 1180-1220°C, more preferably 1200-1210°C; the calcination time is preferably 1.8-2.5h, more preferably 2-2.3h. In the present invention, the calcination is preferably carried out in a muffle furnace.
[0043] In the present invention, the Mg2SiO4 can improve the reduction resistance of the ceramic material and make the temperature coefficient of the ceramic material positive.
[0044] Based on the mass fraction of SrZrO3, the ceramic material provided by the present invention comprises 2.55 to 3.60 parts of SrTiO3, preferably 2.65 to 3.15 parts. In the present invention, the preparation method of SrTiO3 preferably comprises the following steps:
[0045] SrCO3 and TiO2 are mixed and calcined to obtain the SrTiO3.
[0046] In the present invention, the SrCO3 is preferably analytically pure, and the TiO2 is preferably analytically pure. In the present invention, the molar ratio of SrCO3 and TiO2 is preferably 1:1. In the present invention, the mixing is preferably carried out under ball milling conditions. In the present invention, the dispersant for ball milling is preferably water, and the water is preferably deionized water. In the present invention, the grinding balls for ball milling are preferably zirconia balls; the rotation speed of the ball mill is preferably 190 to 210 rpm, more preferably 200 rpm; the ball milling time is preferably 5 to 6 hours, more preferably 5.5 to 5.8 hours.
[0047] In the present invention, after the ball milling, the process preferably further comprises: drying the ball milled mixture. In the present invention, the drying is preferably oven drying, and the oven drying temperature is preferably 110 to 120° C., more preferably 115 to 118° C.; the oven drying time is preferably 6 to 8 hours, more preferably 6.5 to 7 hours. In the present invention, the oven drying is preferably carried out in an oven.
[0048] In the present invention, the calcination temperature is preferably 1080-1120°C, more preferably 1100-1110°C; the calcination time is preferably 2-3 hours, more preferably 2.5-2.8 hours. In the present invention, the calcination is preferably carried out in a muffle furnace.
[0049] In the present invention, the SrTiO3 can increase the dielectric constant of the ceramic material and adjust the temperature coefficient of the ceramic material.
[0050] In order to simplify the preparation steps, the present invention preferably mixes SrCO3, TiO2 and ZrO2 and then calcines them to obtain a mixture of SrZrO3 and SrTiO3.
[0051] In the present invention, the molar ratio of SrCO3, TiO2 and ZrO2 is preferably designed according to the content of SrZrO3 and SrTiO3 in each formula. In the present invention, the mixing is preferably carried out under ball milling conditions. In the present invention, the dispersant for ball milling is preferably water, and the water is preferably deionized water. In the present invention, the grinding balls for ball milling are preferably zirconia balls; the rotation speed of the ball mill is preferably 190 to 210 rpm, more preferably 200 rpm; the time of the ball milling is preferably 7 to 9 hours, more preferably 7.5 to 8.5 hours.
[0052] In the present invention, the ball milling step preferably further comprises: drying the ball milled mixture. In the present invention, the drying step is preferably oven drying, and the oven drying temperature is preferably 110 to 120° C., more preferably 115 to 118° C.; the oven drying time is preferably 6 to 8 hours, more preferably 6.5 to 7 hours.
[0053] In the present invention, the calcination temperature is preferably 1180-1220°C, more preferably 1200-1210°C; the calcination time is preferably 2-3 hours, more preferably 2.5-2.8 hours. In the present invention, the calcination is preferably carried out in a muffle furnace.
[0054] Based on the mass fraction of SrZrO3, the ceramic material provided by the present invention includes 0.8 to 4.1 parts of the modifier, preferably 1.35 to 3.3 parts, and more preferably 1.7 to 2.9 parts. In the present invention, the modifier preferably includes 0.2 to 0.4 parts of MnO2, and more preferably 0.3 to 0.35 parts, by mass fraction.
[0055] Based on the mass fraction of MnO2, the modifier preferably includes 0 to 0.5 parts of MgO, and more preferably 0.2 to 0.5 parts.
[0056] Based on the mass fraction of MnO2, the modifier preferably includes 0.6 to 1.2 parts of Y2O3, more preferably 0.65 to 0.9 parts, and further preferably 0.65 to 0.8 parts.
[0057] Based on the mass fraction of MnO2, the modifier preferably includes 0 to 0.6 parts of Dy2O3, more preferably 0.2 to 0.35 parts, and further preferably 0.3 parts.
[0058] Based on the mass fraction of MnO2, the modifier preferably includes 0 to 0.6 parts of Nd2O3, and more preferably 0.2 to 0.6 parts.
[0059] Based on the mass fraction of MnO2, the modifier preferably includes 0 to 0.5 parts of Sm2O3, and more preferably 0.2 to 0.5 parts.
[0060] Based on the mass fraction of MnO2, the modifier preferably includes 0 to 0.8 parts of Al2O3, and more preferably 0.2 to 0.8 parts.
[0061] In the present invention, the mass fractions of at least two of MgO, Dy2O3, Nd2O3, Sm2O3 and Al2O3 cannot be 0 at the same time. In the present invention, at least four of MnO2, MgO, Y2O3, Dy2O3, Nd2O3, Sm2O3 and Al2O3 are preferably mixed to obtain the modifier. The present invention has no special requirements for the mixing, as long as the mixing can be uniform.
[0062] In the present invention, the modifier can improve the reduction resistance and insulation resistivity of the ceramic material; the modifier can reduce the loss of the ceramic material.
[0063] Based on the mass fraction of SrZrO3, the ceramic material provided by the present invention includes 8.00 to 10.5 parts of sintering aid, preferably 9 to 10.5 parts. In the present invention, the sintering aid preferably includes 5 to 9 parts of Li2CO3, more preferably 7 to 8 parts, by mass fraction.
[0064] Based on the mass fraction of Li2CO3, the sintering aid preferably includes 15 to 25 parts of H3BO3, and more preferably 20 to 22 parts.
[0065] Based on the mass fraction of Li2CO3, the sintering aid preferably includes 35 to 50 parts of BaCO3, and more preferably 35 to 40 parts.
[0066] Based on the mass fraction of Li2CO3, the sintering aid preferably includes 3 to 10 parts of ZnO, and more preferably 3 to 6 parts.
[0067] Based on the mass fraction of Li2CO3, the sintering aid preferably includes 10 to 25 parts of SiO2, and more preferably 15 to 20 parts.
[0068] In the present invention, the preparation method of the sintering aid preferably comprises the following steps:
[0069] The lithium source, boron source, barium source, zinc source and silicon source are mixed according to the element ratio in the sintering aid and calcined to obtain the sintering aid. In the present invention, the lithium source preferably includes Li2O or Li2CO3, and more preferably Li2CO3. In the present invention, the boron source preferably includes B2O3 or H3BO3, and more preferably H3BO3. In the present invention, the barium source preferably includes BaO or BaCO3, and more preferably BaCO3. In the present invention, the zinc source is preferably ZnO. In the present invention, the silicon source is preferably SiO2. In the present invention, when the raw material contains a non-oxide of a metal, it will be converted into a metal oxide during the subsequent calcination process.
[0070] In the present invention, the mixing is preferably carried out under ball milling conditions. In the present invention, the ball milling dispersant is preferably water, and the water is preferably deionized water. In the present invention, the grinding balls for ball milling are preferably zirconia balls; the rotation speed of the ball mill is preferably 290 to 310 rpm, more preferably 300 rpm; the ball milling time is preferably 4.5 to 5.5 hours, more preferably 5 hours.
[0071] In the present invention, after the ball milling, the process preferably further comprises: drying the ball milled mixture. In the present invention, the drying is preferably oven drying, and the oven drying temperature is preferably 80 to 90°C, more preferably 85°C; the oven drying time is preferably 9 to 11 hours, more preferably 10 hours. In the present invention, the drying is preferably carried out in an oven. In the present invention, the dried product is preferably passed through an 80-mesh sieve, and the sieve underfill is taken.
[0072] In the present invention, the calcination temperature is preferably 550-590° C., more preferably 570-580° C.; the calcination time is preferably 2.5-3.5 h, more preferably 3-3.3 h.
[0073] In the present invention, the calcination preferably further comprises: grinding the calcined product after cooling. In the present invention, the temperature after cooling is preferably 20 to 35°C, more preferably 25 to 30°C. In the present invention, the cooling is preferably furnace cooling. The present invention has no special requirements for the grinding, and the conventional method in the art can be used. In the present invention, the ground product is preferably passed through a 100 mesh sieve to take the sieve underfill.
[0074] In the present invention, the sintering aid is a glass substance.
[0075] In the present invention, the sintering aid can reduce the sintering temperature of the ceramic material, so that the ceramic material can be sintered into porcelain at 1050°C.
[0076] In the present invention, the selection of the sintering aid needs to ensure the following principles: (a) the addition of the sintering aid needs to ensure the basic properties of the ceramic material system and cannot deteriorate the electrical properties of the ceramic material system; (b) the sintering aid must match the casting process and must ensure that a qualified and usable cast film can be cast; (c) the sintering aid must be stable or applicable and cannot have obvious component segregation, and when it is co-fired with the copper inner electrode, no large amount of material can be precipitated on the surface of the capacitor.
[0077] In the present invention, Li2O, B2O3 and ZnO have low melting points, which facilitates low-temperature sintering. However, B2O3 undergoes a "complexation" reaction during tape casting, resulting in rough tape-casting abrasive sheets. Li2O and ZnO are easy to precipitate. By adding a certain amount of BaO and SiO2, their "stability" can be improved to a certain extent, thus achieving the role of a sintering aid.
[0078] The present invention also provides a method for preparing the ceramic material described in the above technical solution, comprising the following steps:
[0079] The ceramic material is obtained by mechanically mixing SrZrO3, Mg2SiO4, SrTiO3, a modifier and a sintering aid.
[0080] In the present invention, the mixing is preferably carried out under ball milling conditions. In the present invention, the ball milling dispersant is preferably water, and the water is preferably deionized water. In the present invention, the grinding balls for ball milling are preferably zirconia balls; the rotation speed of the ball mill is preferably 190 to 210 rpm, more preferably 200 rpm; the ball milling time is preferably 4.5 to 5.5 hours, more preferably 5 hours.
[0081] In the present invention, the ball milling preferably further comprises: drying the ball milled mixture. In the present invention, the drying is preferably oven drying, and the oven drying temperature is preferably 110 to 130°C, more preferably 120°C; the oven drying time is preferably 5.5 to 6.5 hours, more preferably 6 hours. In the present invention, the drying is preferably carried out in an oven. In the present invention, the dried product is preferably ground and passed through a 40-mesh sieve to take the sieve-less material.
[0082] The present invention also provides the use of the ceramic material described in the above technical solution or the ceramic material prepared by the preparation method described in the above technical solution in a multilayer ceramic capacitor. In the present invention, the electrodes in the multilayer ceramic capacitor are copper electrodes. The present invention has no special requirements for the method of preparing a multilayer ceramic capacitor using ceramic materials as raw materials, and the conventional method in the art can be used.
[0083] In order to further illustrate the present invention, the technical solutions provided by the present invention are described in detail below in conjunction with embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0084] Example 1
[0085] Analytically pure SrCO3 and analytically pure ZrO2 were placed in a ball mill at a molar ratio of 1:1, with zirconium oxide balls as grinding balls and deionized water as dispersant, and ball milled at a speed of 200 rpm for 8 hours; the ball-milled mixture was dried at 115°C for 6.5 hours and then calcined at 1200°C for 2.5 hours to obtain SrZrO3;
[0086] Analytical pure Mg(OH)2 and analytical pure SiO2 were placed in a ball mill at a molar ratio of 2:1, with zirconium oxide balls as grinding balls and deionized water as dispersant, and ball milled at a speed of 200 rpm for 5.5 hours; the ball-milled mixture was dried at 115°C for 6.5 hours and then calcined at 1200°C for 2 hours to obtain Mg2SiO4;
[0087] Analytically pure SrCO3 and analytically pure TiO2 were placed in a ball mill at a molar ratio of 1:1, with zirconium oxide balls as grinding balls and deionized water as dispersant, and ball milled at a speed of 200 rpm for 6 hours; the ball-milled mixture was dried at 115°C for 7 hours and then calcined at 1100°C for 3 hours to obtain SrTiO3;
[0088] Mix 0.2 g of MnO2, 0.6 g of Y2O3, 0.35 g of Dy2O3, and 0.2 g of MgO to obtain a modifier;
[0089] 5g Li2CO3, 20g H3BO3, 10g ZnO, 40g BaCO3 and 25g SiO2 were placed in a ball mill, with zirconium oxide balls as grinding balls and deionized water as dispersant, and ball milled at a speed of 300rpm for 5h; the ball-milled mixture was dried at 85℃ for 10h and then ground through an 80-mesh sieve, the sieved material was calcined at 570℃ for 3h and then cooled to 30℃ in the furnace; the cooled product was ground through a 100-mesh sieve, and the sieve material was taken to obtain a sintering aid, which was recorded as LBZBS-1;
[0090] 79.8g SrZrO3, 17.55g Mg2SiO4, 2.65g SrTiO3, 1.35g modifier and 10.5g sintering aid were placed in a grinding jar with zirconia balls as grinding balls and deionized water as dispersant, and ball-milled at a rotation speed of 200rpm for 5h; the ball-milled mixture was dried at 120℃ for 6h and then ground through a 40-mesh sieve to obtain a ceramic material.
[0091] Embodiments 2 to 8
[0092] Sintering aids with different compositions were prepared according to the method of Example 1, and their specific compositions are listed in Table 1. Ceramic materials were prepared according to the method of Example 1, and the amounts of components of the ceramic materials were shown in Table 2.
[0093] Table 1 Specific composition of sintering aids
[0094] Sintering Aids LBZBS-1 LBZBS-2 LBZBS-3 LBZBS-4 <![CDATA[Li2CO3 (parts)]]> 5.00 8.00 9.00 7.00 <![CDATA[H3BO3 (parts)]]> 20.00 22.00 25.00 15.00 ZnO (parts) 10.00 10.00 6.00 3.00 <![CDATA[BaCO3 (parts)]]> 40.00 50.00 35.00 50.00 <![CDATA[Silicon dioxide (parts)]]> 25.00 10.00 25.00 25.00
[0095] Table 2 Specific composition of ceramic materials prepared in Examples 1 to 8
[0096]
[0097]
[0098] The performance of the ceramic materials prepared in Examples 1 to 8 was evaluated as follows: 2 g of the ceramic material was mixed with 1.0 mL of a 6.5 wt% polyvinyl alcohol (PVA) aqueous solution and granulated, pressed into a 13 mm disc at 200 MPa, sintered at 1030°C in a nitrogen and hydrogen reducing atmosphere, cooled to 25°C in a furnace after 2 hours, polished and cleaned the sample (removing foreign matter on the surface), and coated and sintered the electrode. After the disc capacitor was made, the capacitance and loss were tested under 1 MHz and 1.0 V using an LCR bridge tester; the insulation resistance was tested under a voltage of 100 V using an insulation resistance tester, and the relative dielectric constant, insulation resistivity and temperature coefficient were calculated, and the results are listed in Table 3.
[0099] Table 3 Properties of ceramic materials prepared in Examples 1 to 8
[0100]
[0101] It can be seen from the performance parameters in Table 3 that the performance of the wafers prepared from the ceramic materials prepared in Examples 1 to 8 can meet the C0G characteristics.
[0102] The ceramic materials of Example 1 and Example 6 were subjected to batching, casting, printing, lamination, uniform pressing, debinding, sintering (sintering temperature 1030°C), chamfering, end coating, end sintering, and electroplating to obtain an MLCC chip with a capacity of 47pF. The capacitance and loss were tested under the conditions of 1MHz and 1.0v using an LCR bridge tester; the insulation resistance was tested under a voltage of 100v using an insulation resistance tester; and the ESR of the MLCC was tested using a radio frequency impedance analyzer. The results are listed in Table 4.
[0103] Table 4 Performance of MLCCs prepared from ceramic materials of Example 1 and Example 6
[0104]
[0105] It can be seen from the data in Table 4 that the MLCC prepared by Example 1 and Example 6 can meet the C0G characteristics, and the loss and insulation resistance can meet the market requirements.
[0106] Embodiments 9 to 16
[0107] The ceramic material was prepared according to the method of Example 1. The amounts of components of the ceramic material were referred to in Table 5.
[0108] Table 5 Specific composition of ceramic materials prepared in Examples 9 to 16
[0109]
[0110]
[0111] The performance of the ceramic materials prepared in Examples 9 to 16 was evaluated as follows: 2 g of the ceramic material was mixed with 1.0 mL of a 6.5 wt% polyvinyl alcohol (PVA) aqueous solution and granulated, pressed into a 13 mm disc at 200 MPa, sintered at 1030°C in a nitrogen-hydrogen reducing atmosphere, cooled to 25°C in the furnace after 2 hours, polished and cleaned the sample, and coated and sintered the electrode. After the disc capacitor was made, the capacitance and loss were tested under the conditions of 1 MHz and 1.0 V using an LCR bridge tester; the insulation resistance was tested under a voltage of 100 V using an insulation resistance tester, and the relative dielectric constant, insulation resistivity and temperature coefficient were calculated, and the results are listed in Table 6.
[0112] Table 6 Properties of ceramic materials prepared in Examples 9 to 16
[0113]
[0114]
[0115] It can be seen from the performance parameters in Table 6 that the performance of the wafers prepared from the ceramic materials prepared in Examples 9 to 16 can meet the C0G characteristics.
[0116] The ceramic materials of Example 11 and Example 15 were subjected to batching, casting, printing, lamination, uniform pressing, debinding, sintering (sintering temperature 1030°C), chamfering, end coating, end sintering and electroplating to obtain an MLCC chip with a capacity of 47pF. The capacitance and loss were tested under the conditions of 1MHz and 1.0v using an LCR bridge tester; the insulation resistance was tested under a voltage of 100v using an insulation resistance tester; and the ESR of the MLCC was tested using a radio frequency impedance analyzer. The results are listed in Table 7.
[0117] Table 7 Performance of MLCCs prepared from ceramic materials of Example 11 and Example 15
[0118]
[0119] It can be seen from the data in Table 7 that the MLCC prepared by Example 11 and Example 15 can meet the C0G characteristics, and the loss and insulation resistance can meet the market requirements.
[0120] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. People can also obtain other embodiments based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.
Claims
1. A ceramic material, characterized in that: The composition comprises the following components in parts by weight: SrZrO3 79.8~96.1 parts; Mg2SiO4 0.63~17.55 parts; SrTiO3 2.55~3.60 parts; Modifier 0.8~4.1 parts; Sintering aid 8.00~10.5 parts; The modifier comprises the following components in parts by mass: MnO2 0.2~0.4 parts; MgO 0~0.5 parts; Y2O3 0.6~1.2 parts; Dy2O3 0~0.6 parts; Nd2O3 0~0.6 parts; Sm2O3 0~0.5 parts; Al2O3 0~0.8 parts; The mass fractions of at least two substances among MgO, Dy2O3, Nd2O3, Sm2O3 and Al2O3 cannot be 0 at the same time; The sintering aid comprises the following components in parts by weight: Li2CO3 5~9 parts; H3BO3 15~25 parts; BaCO3 35~50 parts; ZnO 3~10 parts; SiO2 10~25 parts.
2. The ceramic material according to claim 1, characterized in that: The preparation method of the sintering aid comprises the following steps: The lithium source, boron source, barium source, zinc source and silicon source are mixed according to the element ratio in the sintering aid and then calcined to obtain the sintering aid; the calcination temperature is 550-590° C. and the calcination time is 2.5-3.5 hours.
3. The method for preparing the ceramic material according to claim 1 or 2, comprising the following steps: The ceramic material is obtained by mechanically mixing SrZrO3, Mg2SiO4, SrTiO3, a modifier and a sintering aid.
4. The method for preparing the ceramic material according to claim 3, characterized in that: The preparation method of SrZrO3 comprises the following steps: SrCO3 and ZrO2 are mixed and calcined to obtain the SrZrO3; The calcination temperature is 1180-1220° C., and the calcination time is 2-3 hours.
5. The method for preparing the ceramic material according to claim 3, characterized in that: The preparation method of Mg2SiO4 The following steps are involved: Mixing Mg(OH)2 and SiO2 and calcining them to obtain the Mg2SiO4; The calcination temperature is 1180-1220° C., and the calcination time is 1.8-2.5 h.
6. The method for preparing the ceramic material according to claim 3, characterized in that: The preparation method of SrTiO3 comprises the following steps: SrCO3 and TiO2 are mixed and calcined to obtain the SrTiO3; The calcination temperature is 1080-1120° C., and the calcination time is 2-3 hours.
7. Use of the ceramic material according to claim 1 or 2 or the ceramic material prepared by the preparation method according to any one of claims 3 to 6 in a multilayer ceramic capacitor.
8. The use according to claim 7, characterized in that: The electrodes in the multilayer ceramic capacitor are copper electrodes.
Citation Information
Patent Citations
Low-sintering microwave dielectric ceramic material and preparation method thereof
CN111320473A